The Role of Hemodialysis in Toxicology including neonates: A Systematic Review - Sivasankar, M.; Niranjan Raja, I; Parthasarathy, S. (Journal of Neonatal Surgery, 2025)
Background: The management of poisoned patients often is complicated by the need for renal replacement therapies, particularly hemodialysis, to effectively address acute poisonings complicated by renal dysfunction. Objective: This systematic review synthesizes current literature concerning the use of hemodialysis in toxicology, assessing its effectiveness at toxin clearance and its association with complications. Methods: A literature search was conducted across major databases, including PubMed, Embase, Cochrane Library, and Web of Science, focusing on articles published from January 2000 to October 2023 that analyze hemodialysis for toxic substance removal. Data extraction prioritized toxin types, patient demographics, hemodialysis specifics, and clinical outcomes. Results: Hemodialysis is most effective for water-soluble and minimally protein-bound toxins like acetaminophen, lithium, salicylates, methanol, and ethylene glycol. Its effectiveness decreases with highly protein-bound substances, those with a high volume of distribution, and volatile compounds. Inborn errors of metabolism can cause toxic metabolite buildup, affecting neonatal brain development. A study of 20 cases showed that timely hemodialysis improved clinical outcomes in 85% of patients. Common complications include hypotension, infections, and electrolyte imbalances, which require close monitoring and tailored interventions. Conclusion: Hemodialysis is an important tool in the management of toxicological emergencies. However, the success of hemodialysis is dependent on many factors, including the characteristics of the toxin and the patient's health status. Recent advances in dialysis membranes and Continuous Renal Replacement Therapy have improved its use in such cases. However, there are limitations to its use, and alternative treatment strategies must be considered for some poisonings. This review discusses kidney replacement therapy options, challenges for infants, and the importance of informed catheter use by interventional radiologists.